EVALUASI PROGRAM BIMBINGAN BELAJAR MATEMATIKA DAN UTBK LEMBAGA BIMBINGAN BELAJAR NON-PROFIT DI PEKALONGAN - Ramadian Radite; Eka Sulistyawati; Andika Nugraha Firmansyah (Jurnal Evaluasi Pendidikan, 2022)
ABSTRACT Educational programs, whether formal, non-formal, for-profit or non-profit, have the aim of organizing educational activities. In Pekalongan, to be precise in the Medono area, there is a non-profit learning institution that has programs such as mathematics classes and UTBK. Evaluation needs to be carried out to determine the effectiveness of program implementation and to provide consideration for decisions regarding the sustainability of the program. Program evaluation used the Responsive model evaluation from Stake which consists of antecedent, transaction, and outcomes/process stages with a qualitative approach. The data collection technique used a questionnaire for study participants, tutors, parents of study participants, and the community around the institution. The evaluation results show that the program has been implemented based on the interests, talents, and needs of the participants and tutors by collaborating through discussions, questions and answers, and being a teacher for their friends. The program results showed an increase in participant achievement, participants studying the UTBK class achieved their goals of being accepted at the desired university, increased collaboration skills, benefits received by tutors, and good reception from participants' parents and the community. Keywords evaluation, program, interest, collaboration, everyone is a teacher ABSTRAK Program pendidikan baik formal, non-formal, profit maupun non-profit memiliki tujuan menyelenggarakan kegiatan pendidikan. Di Pekalongan tepatnya daerah Medono terdapat lembaga belajar non-profit yang memiliki berbagai program seperti kelas matematika dan UTBK. Evaluasi perlu dilakukan untuk mengetahui efektivitas pelaksanaan program, apakah program mencapai tujuan, dan memberikan pertimbangan keputusan mengenai keberlangsungan program. Evaluasi program menggunakan evaluasi model Responsive dari Stake yang terdiri dari tahap antecedent, transaction, dan outcomes/process dengan pendekatan kualitatif. Teknik pengambilan data menggunakan kuesioner untuk peserta belajar, tutor, orang tua peserta belajar, dan masyarakat sekitar lembaga. Hasil evaluasi menunjukkan bahwa program telah dijalankan berdasarkan minat, bakat, maupun kebutuhan peserta belajar dan tutor dengan berkolaborasi melalui diskusi, tanya jawab, dan menjadi guru bagi temannya. Hasil dari program menunjukkan adanya peningkatan prestasi peserta, peserta belajar kelas UTBK mencapai cita-cita diterima di Perguruan Tinggi yang diincar, peningkatan kemampuan kolaborasi, manfaat yang diterima oleh tutor, serta sambutan baik dari orang tua peserta dan masyarakat. Kata Kunci evaluasi, program, minat, kolaborasi, everyone is a teacher